2023
DOI: 10.1007/s40820-023-01075-9
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Self-Healing Chemistry for Next-Generation Flexible Energy Storage Devices

Abstract: The booming wearable/portable electronic devices industry has stimulated the progress of supporting flexible energy storage devices. Excellent performance of flexible devices not only requires the component units of each device to maintain the original performance under external forces, but also demands the overall device to be flexible in response to external fields. However, flexible energy storage devices inevitably occur mechanical damages (extrusion, impact, vibration)/electrical damages (overcharge, over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 179 publications
0
10
0
Order By: Relevance
“…The decreased R s value can be attributed to the fact that the added artificial sweat increased the concentration of NaCl, resulting in an increase of the ionic conductivity of the electrolyte. This application demonstrates the feasibility of self-healing supercapacitors for developing wearable electronics suitable for daily use. …”
Section: Resultsmentioning
confidence: 99%
“…The decreased R s value can be attributed to the fact that the added artificial sweat increased the concentration of NaCl, resulting in an increase of the ionic conductivity of the electrolyte. This application demonstrates the feasibility of self-healing supercapacitors for developing wearable electronics suitable for daily use. …”
Section: Resultsmentioning
confidence: 99%
“…Considering these challenges, intrinsic self-healing polymeric materials have become a research hotspot due to their significantly improved service lives and safety in practical applications, capable of automatically restoring their original performance after being damaged by external factors. 18,19 Previous studies have confirmed that introducing self-healing systems into EMI shielding materials could effectively address the decreased electromagnetic shielding performance caused by mechanical damages. For instance, Sim et al 20 demonstrated that the EMI SE of a damaged graphene oxide/silver nanowire film decreased from 72 dB to 56 dB but was restored to 71 dB after healing treatment.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, high fossil fuel consumption leads to environmental pollution and harms human beings. 2 Notably, electricity is an economical and practical clean energy source; hence, there has been a recent surge in demand for electrochemical energy storage systems. 3 Additionally, supercapacitors have attracted increasing attention due to their superior power density, rapid charge and discharge rates, and extensive lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, contemporary energy supply is excessively dependent on the rapid consumption of nonrenewable fossil fuels, including coal, natural gas, and petroleum, resulting in their swift depletion. Furthermore, high fossil fuel consumption leads to environmental pollution and harms human beings . Notably, electricity is an economical and practical clean energy source; hence, there has been a recent surge in demand for electrochemical energy storage systems .…”
Section: Introductionmentioning
confidence: 99%